Risk of Pancreatic Cancer in Female Textile Workers in Shanghai, China, Exposed to Metals, Solvents, Chemicals, and Endotoxin: Follow-Up to a Nested Case-Cohort Study. Issue 2 (February 2016) - Reul, Nicholas K.; Li, Wenjin; Gallagher, Lisa G.; Ray, Roberta M.; Romano, Megan E.; Gao, Daoli; Thomas, David B.; Vedal, Sverre; Checkoway, Harvey
Abstract : Objective: We studied associations between pancreatic cancer and occupational exposures to metals, solvents, chemicals, and endotoxin in a cohort of female textile workers in Shanghai, China. To assess the longer-term influences of these agents on pancreatic cancer we extended follow-up of this previously studied cohort. Methods: We utilized a job exposure matrix to assess occupational exposures for 481 pancreatic cancer cases and a randomly selected sub-cohort of 3191 non-cases. We calculated hazard ratios and 95% confidence intervals using Cox proportional hazards modeling adapted for the case-cohort design. Results: We observed a statistically significant trend of increasing hazard ratios associated with solvent exposure, but no associations with any of the remaining occupational exposures, including endotoxin and metals. Conclusions: Our findings of increasing risk of pancreatic cancer with solvent exposures are consistent with published literature.